Echocardiographic reference intervals for end-diastolic and end-systolic left ventricle volumes obtained by Simpson’s method of discs in healthy showjumping and polo Argentinian Saddlebred horses - Perez, Jeff; Alessi, Chiara; Giraldo, Carlos E.; Zucca, Enrica; Wess, Gerhard; Linares, Sergio (Archives of Veterinary Science, 2024)
The left ventricle volume quantification is a critical component of standard echocardiography. Therefore, this study aimed to establish breed-specific echocardiographic reference intervals for end-diastolic and end-systolic volumes using Simpson’s method of discs (SMOD) in healthy showjumping and polo Argentinian Saddlebred horses. The central 90% reference limit was calculated, and its confidence and reference intervals were reported with 90% confidentiality. A comparison was performed between cardiac SMOD-derived and Teichholz-derived volumes and between males and females. A total of 117 horses (43 females and 77 males) weighing 445–690 kg (521 ± 56 kg) with similar training were selected to create the reference intervals. SMOD-derived end-diastolic volume indexed (EDVI) was 1.32 ml/kg, RI from 1.26 to 1.37 ml, and SMOD-derived end-systolic volume indexed (ESVI) was 0.47 ml/kg, RI from 0.43 to 0.50 ml. There was a significant difference between EDVI SMOD-derived and EDVI Teichholz-derived volumes (p < 0.001, d = 1.14). In addition, ESVI SMOD-derived volumes differed from Teichholz-derived volumes (p < 0.05, r = 0.33). EDVI was statistically similar between males and females (p = 0.721). ESVI was statistically similar between males and females (p = 0.122). In conclusion, it is feasible and reproducible to obtain SMOD-derived volumes in horses as in humans and dogs with standard views modifications and reference intervals are reported for clinical and research purposes, especially when accurate quantification of ventricular volumes and ejection fraction are needed. Keywords: Horses, cardiac volumes, echocardiography, left ventricle, reference intervals